Irish shame a literary reckoning - Kennedy, Seán 1974-; Valente, Joseph 1958- (Edinburgh University Press, 2025)
"The first edited collection dedicated to the historical specifics of Irish shame Offers an anatomy of Irish shame as a cultural predicament Combines theoretical reading with historical and institutional context Includes essays by some of Ireland’s leading researchers on trauma and sexuality studies Shame has haunted Ireland since the inception of Irishness itself. As such, it has come to seem an ineluctable modality of Irish life. In fact, the contours of Irish shame have evolved over time, shifting with alterations in their colonial predicament, and in their response, whether complicit or resistant, to economic, political, and cultural dispossession. Irish Shame offers an anatomy of that condition. In twelve essays, it traces the ethnic, religious, biopolitical, psychosocial and neurodiverse parameters of shame as a force in Irish life."
Keywords: Shame / Ireland / History; Shame in literature; Ethics in literature; National characteristics, Irish; Irish literature / History and criticism